Preliminary findings in the heart rate variability and haemorheology response to varied frequency and duration of walking in women 65–74 yr with type 2 diabetes - Simmonds, Michael J.; Minahan, Clare L.; Serre, Kevin R.; Gass, Gregory C.; Marshall-Gradisnik, Sonya M.; Haseler, Luke J.; Sabapathy, Surendran (Clinical hemorheology and microcirculation, 2012)
Heart rate variability (HRV) and haemorheology adaptations to 12 wk of varied-dose treadmill walking were investigated in women aged 65–74 yr with type 2 diabetes. Subjects were randomly allocated into two groups where exercise frequency and session duration were manipulated (Group 1 : 2 × 60 min·wk−1 or Group 2 : 4 × 30 min·wk−1), but intensity and accumulated weekly duration of exercise were consistent between groups (100% gas-exchange threshold; 120 min·wk−1). Twelve weeks of exercise training significantly improved peak oxygen uptake, time to exhaustion, and gas-exchange threshold (p < 0.05), independent of exercise group. Exercise training did not significantly change glycaemic control or body mass. Red blood cell (RBC) aggregation and RBC deformability significantly decreased (p < 0.05) for both groups. No change in HRV was observed for Group 1, whereas several key indicators of HRV were significantly improved in Group 2 (p < 0.05). The present study was the first to report decreased RBC aggregation following an exercise-only intervention and that exercise training improved RBC aggregation without a concomitant improvement in glycaemic control. The accumulated weekly exercise duration may be the most important training component for the prescription of exercise in older women with type 2 diabetes.